In silico identification of chilli genome encoded MicroRNAs targeting the 16S rRNA and secA genes of “Candidatus phytoplasma trifolii” - Pandey, Vineeta; Srivastava, Aarshi; Gupta, Ramwant; Zaki, Haitham E. M.; Shafiq Shahid, Muhammad; Gaur, Rajarshi K. (Frontiers in Bioinformatics, 2025)
Phytoplasma, a potentially hazardous pathogen associated with witches’ broom, is an economically harmful disease-producing bacteria that damages chilli cultivation. Phytoplasma-infected plants display various symptoms that indicate significant disruptions in normal plant physiology and behaviour. Diseases caused by phytoplasma are widespread and have a major economic impact on crop quality and yield. This work focuses on identifying and examining chilli microRNAs (miRNAs) as potential targets against the 16S rRNA and secA gene of “Candidatus Phytoplasma trifolii” (“Ca. P. trifolii”) through plant miRNA prediction algorithms. Mature chilli miRNAs (CA-miRNAs) were collected and used to hybridise the 16S rRNA and secA genes. A total of four common CA-miRNAs were picked according to genetic consensus. Three algorithms applied in the present study suggested that the physiologically relevant, top-ranked miR169b_2 has a possibly specific site at nucleotide position 1,006 for targeting the ‘Ca. P. trifolii’ 16S rRNA gene. The circos algorithm was then utilised to create the miRNA-mRNA regulatory network. The free energy between the miRNA:mRNA duplex was also computed, and the best value of −17.46 kcal/mol was obtained for CA-miR166c_2. Currently, there are no suitable commercial ‘Ca. P. trifolii’-resistant chilli crops. As a result, the expected biological data provide useful evidence for developing ‘Ca. P. trifolii’-resistant chilli plants.